2021
DOI: 10.1093/jat/bkab071
|View full text |Cite
|
Sign up to set email alerts
|

Methadone, Buprenorphine, Oxycodone, Fentanyl and Tramadol in Multiple Postmortem Matrices

Abstract: Peripheral blood concentrations are generally preferred for postmortem toxicological interpretation, but some autopsy cases may lack blood for sampling due to decomposition or large traumas etc. In such cases, other tissues or bodily fluids must be sampled; however, limited information exists on postmortem concentrations in matrices other than blood. Pericardial fluid, muscle, and vitreous humor have been suggested as alternatives to blood, but only a few studies have investigated the detection of opioids in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…This indicates that if the concentration in blood increases, the concentration in the alternative matrix also increases. Opioids are some of the most studied analytes in paired samples of peripheral blood and alternative matrices in the literature, where their concentration ratios in brain tissue, 21,27,32,35,[39][40][41] cardiac blood, [8][9][10]12,16,[40][41][42][43] and muscle tissue relative to peripheral blood 10,23,[40][41][42][44][45][46] are either reported or can be calculated from the concentrations. Even though some of the studies include many cases, there is a lack of consensus in the concentration ratios reported, with wide ranges generally being observed and the mean and median differing between studies.…”
Section: Opioidsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that if the concentration in blood increases, the concentration in the alternative matrix also increases. Opioids are some of the most studied analytes in paired samples of peripheral blood and alternative matrices in the literature, where their concentration ratios in brain tissue, 21,27,32,35,[39][40][41] cardiac blood, [8][9][10]12,16,[40][41][42][43] and muscle tissue relative to peripheral blood 10,23,[40][41][42][44][45][46] are either reported or can be calculated from the concentrations. Even though some of the studies include many cases, there is a lack of consensus in the concentration ratios reported, with wide ranges generally being observed and the mean and median differing between studies.…”
Section: Opioidsmentioning
confidence: 99%
“…Thus, peripheral blood is the primary choice of specimen for postmortem analysis. To evaluate the degree of PMR, concentrations in central blood are compared with concentrations in peripheral blood from authentic cases 4,8–11 . Systematic studies have compared concentrations measured upon morgue admission and at autopsy, where a high concentration ratio between the two sampling time points suggests a high degree of PMR 12–16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these matrices remain stable for a long time even after death [85]. A few studies have been reported in describing the determination of BUP, MTD and their metabolites in VH and skeletal tissue [39,74,85]. They concluded that VH and skeletal tissue are particularly important alternative matrices for post-mortem biochemical investigations.…”
Section: Biological Matricesmentioning
confidence: 99%
“…Different biological specimens including urine [7,, plasma [13,20,21,35,38,40,[42][43][44][45][46][47][48][49][50][51][52][53][54][55], serum [30,[56][57][58][59], blood [15,18,22,49,[60][61][62][63], nails [64], oral fluid [17,31,55,[65][66][67][68][69], hair [47,[70][71][72], tissue [73,74] and exhaled breath condensate [75,76] have been used for the measurement of BUP, MTD and their metabo...…”
Section: Introductionmentioning
confidence: 99%